SURGICAL TREATMENT OF UPWARD PATELLAR FIXATION OF IN BUFFALOES OF BASRAH PROVINCE - Abdalbari A. alfars (Basrah Journal of Veterinary Research)
A study was conducted on 65 clinical cases of upward fixation of patella of she buffaloes treated during the last years(2000 - 2006). The occurrence of the disease with respect to species and season were documented Buffaloes suffering from jerky movement during flexion to complete immobilization of the joint. Since the animal fixes its( limb in extension ) while the patella glides up over the trochela. All Buffaloes were affected with upward fixation of the patella in one back leg.